Earthquake Sensor Microcontroller Using Mma7361 Accelerometer - ., Laumal; E., Folkes (International Journal of Engineering and Technology, 2019)
Vibrations propagate to the surface of the earth in two stages. The first stage is called the Primary wave-shaped longitudinal and the second stage is secondary wave, sinusoidal and destructive. The second wave did not come together so that there is a certain amount of time intervals. This time interval can be utilized to provide early warning from earthquake sensors microcontrollers. As registrar, earthquake seismograph always inform the level of earthquake damage in form of scales, but did not provide early warning. While the microcontroller and sensor technology developed and were able to catch the tremor.This study aims to build earthquake microcontroller sensors to capture the primary seismic vibrations quickly. The study focused on the sensor design, calibration and data transmission, while the primary wave simulation given experimentally by treatment of vibration on the sensor that is connected to computer and displays the initial vibration data on computer. The results showed that interconnection MMA7361 accelerometer, EM411 GPS, ATmega328 on Arduino and data processing protocols have produced seismic sensor that captures digital data and data shakes position quickly. In the absence of vibration, the sensor does not provide the data and when vibration, there is transmitting data to computer database.Â Â